Jawabanmu

2014-08-26T13:55:47+07:00
3x (2x - 4) +2 (2x - 4) =
6x kuadrat - 12 x + 4x -8 =
6x kuadrat - 8x -8

a (46) + 2b (46) =
46a + 92b

3x (5x - 39) - 5y (5x - 39) =
15 x kuadrat - 117x - 25yx + 195y

-4p (4p + 6) -6 (4p + 6) =
-16p kuadrat - 24p - 24p - 36
-16p kuadrat - 48p - 36

x (x - 7) +6 (x - 7) =
x kuadrat - 7x + 6x - 42 =
x kuadrat - x - 42


maaf kl salah.
2014-08-26T14:23:39+07:00
1.3x(2x-4)+2(2x-4)
= 6x²+4x-8
2.a(+46)-2b(+46)
=a+46a-2b-92
=47a-2b-92
3.3x(5x-39)-5y(5x-39)
=15x²-107x-25xy+195
4.-4p(4p+6y)-6(4p+6y)
=-16p²-24y-24p-36y
=-24y-36y-16p²-24p
=-60y-16p²-24p
5. x²-7x+6x-42
=x²-x-42